ENERGY UTILIZATION IMPACTS IN DETECTING ABNORMALITY ON WIRELESS SENSOR NETWORKS - Zuhal Can; Elif Değirmenci (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi, 2022)
With the novel developments in Wireless Sensor Network (WSN) technologies, environmental data collection and processing services are applied in diverse industrial and scientific areas. However, energy limitations and vulnerabilities of WSN nodes are still the main drawbacks of technological developments in the area. Understanding the energy utilization patterns of nodes helps to detect abnormal node behaviors and prevent malicious nodes. In this study, we observe the energy utilization behaviors of nodes and found that nodes have distinctive activity patterns based on their types. We also found that source, sink, and relay nodes on the data propagation path have higher energy consumption patterns compared to other nodes